A Cointegration Analysis of Agricultural, Energy and Bio-Fuel Spot and Futures Prices - David E. Allen; Chia-Lin Chang; Michael McAleer; Abhay K. Singh (Tinbergen Institute, 2016)
This paper features an analysis of the cointegration relationships among agricultural commodity, ethanol and Cushing crude oil spot and futures prices. The use of grains for the creation of bio-fuels has sparked fears that these demands are inflating food prices. We analyse approximately 10 years of daily spot and futures prices for corn, wheat, sugar ethanol and oil prices from Datastream for the period 19 July 2006 to 2 July 2015. The analysis, featuring Engle-Granger pairwise cointegration and Markov-switching VECM and Impulse Response Analysis, confirms that these markets have significant linkages which vary according to whether they are in low or high volatility regimes.
Keywords: C22; Q02; Q35; Q42; 330; Bio-fuels; time series; cointegration; Markov-switching; VECM; Impulse Responses; Volatility